Public infrastructure and its importance for economic growth: the case of Oaxaca (Mexico) (2018)
The objective of this paper is to estimate the impact of public infrastructure on economic growth in the eight regions of Oaxaca for the period 2003-2013. Given that regional statistics are lacking, the methodology proposed by Gerber (2003) is used to calculate the economic growth of the regions. And to measure the impact of infrastructure on growth, based on Hoechle (2007) a fixed-effects model with standard errors of Driscoll and Kraay (DKSE) is applied. The results indicate that investment in infrastructure has been insufficient and misallocated; however, the social infrastructure shows the greatest impact on growth. Finally, the results suggest that the most dynamic regions require greater investment in economic infrastructure, while the backward regions need social infrastructure.